Elaboration and refinement of a motivational communication training program for healthcare professionals in pediatric oncology: a feasibility and acceptability study. Issue 1 (1st January 2021) - Dewez, Sébastien; Laurin, Catherine; Ogez, David; Bourque, Claude-Julie; Curnier, Daniel; Laverdière, Caroline; Levesque, Ariane; Marcil, Valérie; Sinnett, Daniel; Sultan, Serge
ABSTRACT: Introduction: A healthy lifestyle could have a positive impact in reducing the incidence of some long-term sequelae secondary to pediatric cancer treatments. Motivational communication (MC) is effective at improving healthy lifestyle habits, especially when patients experience change as a challenge. To date, there is no available intervention program using MC that promotes healthy lifestyles in pediatric oncology. Objectives: The aim of this study was to develop the first MC training program for professionals in pediatric oncology and assess its feasibility and acceptability. Materials and methods: Following standard procedures involving professionals, we developed a professional-targeted training named the Motivation Cafés, consisting in six sessions of core MC skills for healthcare professionals who wish to positively impact lifestyles of families in pediatric oncology. We used a mixed-methods quantitative-qualitative study to assess the program feasibility and acceptability. Professionals in nutrition and physical activity ( N  = 16) attended two rounds of the training and completed surveys to evaluate the training. They reported self-efficacy and knowledge in MC. Participation and retention rates were used to assess acceptability and feasibility, and a thematic analysis of the open-ended questions was performed to identify strengths and weaknesses of the program to further refine the program. We used non-parametric statistics to compare pre-post changes on measures of self-efficacy and knowledge in MC. Results: Attendance and retention (average 4.2/6 sessions completed) were high, suggesting very good adherence and feasibility. We also found high levels of acceptability and pertinence of the program (i.e. >90%). The results suggested probable improvements in self-efficacy and knowledge, but these were not statistically significant given the limited sample size. Conclusion: The training Motivation Cafés is now ready to be pilot tested in pediatric cancer care centers.